The Role of Heritage Architecture in Central: Cultural Conservation or Conversion? Case Study of The “30 Houses” Neighbourhood under Hong Kong’s Conservation Policies, and The Influence of Public Participation on Local Conservation Projects - Kathy, Lau Hei Mun (MAJ - Malaysia Architectural Journal, 2025)
In the context of Hong Kong's intricate historical narrative, the city's heritage, encompassing cultural traditions and architectural remnants, serves as a repository of collective memory and history to be transmitted to future generations. Despite initial neglect post-1997 in favour of economic advancement, a growing emphasis on preserving built heritage has emerged, underscored by pivotal events like the Queen's Pier demolition and Lee Tung Street redevelopment. Presently, although a grading system established by the Antiquities Advisory Board (AAB) exists for historical buildings, only Declared Monuments hold legal protection (Cap. 53 Antiquities and Monuments Ordinance). Challenges persist, notably in balancing preservation with modern needs through initiatives like the Revitalising Historic Buildings Through Partnership Scheme. Noteworthy is Central's juxtaposition of modern skyscrapers with heritage sites, exemplifying the delicate interplay between progress and conservation. As public awareness grows, this paper explores Hong Kong's conservation policies, spotlighting Central as a microcosm, advocating for public engagement and knowledge dissemination to safeguard the city's remaining heritage.